A Higher Antibody Response Is Generated With a 6- to 7-Week (vs Standard) Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) Vaccine Dosing Interval. (30th November 2021) - Grunau, Brian; Asamoah-Boaheng, Michael; Lavoie, Pascal M; Karim, Mohammad Ehsanul; Kirkham, Tracy L; Demers, Paul A; Barakauskas, Vilte; Marquez, Ana Citlali; Jassem, Agatha N; O'Brien, Sheila F; Drews, Steven J; Haig, Scott; et al.
Abstract: The optimal dosing interval for severe acute respiratory syndrome coronavirus 2 vaccines remains controversial. In this prospective study, we compared serology results of paramedics vaccinated with mRNA vaccines at the recommended short (17–28 days) vs long (42–49 days) interval. We found that a long dosing interval resulted in higher spike, receptor binding domain, and spike N terminal domain antibody concentrations.